Analisis Kualitatif Dampak Kepuasan Pelanggan terhadap Keberhasilan Pemasaran Koperasi: Sintesis Studi Literatur - Ferry Sanjaya; Riky Barja (Draf Solusi Indonesia, 2024)
Customer satisfaction significantly impacts the marketing success of cooperatives. Key factors influencing customer satisfaction include service quality, brand image, member value, and trust. Satisfied customers lead to increased member loyalty, sales, profits, and positive reputation. Cooperative principles of democratic member involvement play a crucial role in understanding and meeting customer needs. Effective strategies to enhance customer satisfaction and marketing success involve superior service quality, effective communication, focusing on customer needs, and continuous performance improvement.